Ultrasmall lanthanide oxide nanoparticles for biomedical imaging and therapy - Lee, Gang Ho; Chang, Yongmin; Kim, Tae-Jeong; ScienceDirect eBooks (Cambridge : Woodhead Publishing, 2014)
Most books discuss general and broad topics regarding molecular imagings. However, Ultrasmall Lanthanide Oxide Nanoparticles for Biomedical Imaging and Therapy, will mainly focus on lanthanide oxide nanoparticles for molecular imaging and therapeutics. Multi-modal imaging capabilities will discussed, along with up-converting FI by using lanthanide oxide nanoparticles. The synthesis will cover polyol synthesis of lanthanide oxide nanoparticles, Surface coatings with biocompatible and hydrophilic ligands will be discussed and TEM images and dynamic light scattering (DLS) patterns will be provid.
6 A simple model calculation of water proton relaxivities6.1 Introduction; 6.2 Magnetization; 6.3 Longitudinal water proton relaxation (T1) and relaxivity (r1); 6.4 Transverse water proton relaxation (T2) andrelaxivity (r2); 6.5 Concluding remarks; 6.6 References; 7 Thermal neutron capture therapy (NCT); 7.1 Introduction; 7.2 BNCT; 7.3 GdNCT; 7.4 References; 8 Perspectives and challenges; 8.1 Perspectives and challenges; 8.2 What needs to be done for clinical applications; Index.
CIP data; item not viewed.
Elsevier
Keywords: Diagnostic imaging; Nanotechnology; Nanoparticles; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Diagnostic imaging; Nanoparticles; Nanotechnology; Electronic books